O bibliotecário e o uso da competência informacional: percepções dos estudantes de Biblioteconomia da UFPA - PASSOS JÚNIOR, Jairo Jacques dos (2018)
It approaches the students' perceptions of Library Science about information literacy. It uses the focus group technique and semi-structured interviews. Eleven students from different classes from Librarianship at the Universidade Federal do Pará participated of the focus group. Four people were interviewed: the director of the Faculdade de Biblioteconomia and three students. It analyzes data by the ethical, aesthetic, political and technical dimension of information literacy. It shows that the technical and esthetic dimension are the most present in students' perceptions regarding the concept and role of the librarian in this type of competence. It notes that focal group participants have difficulties in understanding the political and ethical component. It concludes that these dimensions need to be more evident in the discipline Leitura e Competência Informacional.